A weighted transplantation theorem for Laguerre function expansions - Lin Tang (Հայաստանի ԳԱԱ)
We establish a generalized weighted transplantation theorem for Laguerre function expansions, which extends the corresponding result by G. Garrigós et al. "A sharp weighted transplantation theorem for Laguerre function expansions"(J. Funct Anal. 244 (2007), pp. 247-276).
Keywords: Mathematics; Science